2017
DOI: 10.1002/jhet.3019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Pyrimido[4′,5′:3,4]pyrazolo[1,2‐b]phthalazine‐4,7,12‐triones: Derivatives of a New Heterocyclic Ring System

Abstract: Several derivatives of the new pyrimido[4′,5′:3,4]pyrazolo[1,2‐b]phthalazine‐4,7,12‐trione ring system have been prepared by the reaction of 3‐amino‐1‐aryl‐5,10‐dioxo‐5,10‐dihydro‐1H‐pyrazolo[1,2‐b]phthalazine‐2‐carbonitriles with aliphatic carboxylic acids in the presence of phosphoryl chloride (POCl3). The synthesized compounds were characterized on the basis of IR, 1H NMR, and 13C NMR spectral and microanalytical data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Taking all these facts into consideration, and in conjunction with our earlier studies of synthesis of heterocyclic compounds , herein, we report the synthesis of some new derivatives of 6‐alkylamino‐1,3‐diphenyl‐1 H ‐pyrazolo[3,4‐ b ]pyridine‐5‐carbonitrile 4a–f in synthetically useful yields by Knoevenagel condensation of 5‐chloro‐1,3‐diphenyl‐1 H ‐pyrazole‐4‐carbaldehyde 1 with malononitrile 2 in ethanol containing a few drops of glacial acetic acid at reflux temperature, which afforded compound 3 , followed by cyclization with primary alkyl amines in the presence of 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) as catalyst in refluxing ethanol (Scheme ). To the authors' knowledge, compounds 4a–f are new and have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 89%
“…Taking all these facts into consideration, and in conjunction with our earlier studies of synthesis of heterocyclic compounds , herein, we report the synthesis of some new derivatives of 6‐alkylamino‐1,3‐diphenyl‐1 H ‐pyrazolo[3,4‐ b ]pyridine‐5‐carbonitrile 4a–f in synthetically useful yields by Knoevenagel condensation of 5‐chloro‐1,3‐diphenyl‐1 H ‐pyrazole‐4‐carbaldehyde 1 with malononitrile 2 in ethanol containing a few drops of glacial acetic acid at reflux temperature, which afforded compound 3 , followed by cyclization with primary alkyl amines in the presence of 1,8‐diazabicyclo[5.4.0]undec‐7‐ene (DBU) as catalyst in refluxing ethanol (Scheme ). To the authors' knowledge, compounds 4a–f are new and have not been reported in the literature.…”
Section: Introductionmentioning
confidence: 89%